Akibat Hukum Adopsi terhadap Waris Menurut Kompilasi Hukum Islam - Amelia, Risky (Wajah Hukum, 2024)
Children are the fruit of love that every married couple dreams of, but many couples experience challenges in having children. For many husbands and couples who have been married for a long time but have not been blessed with a child, adoption is the best alternative. However, many problems arise as a result of this implementation; One of the roots of the problem is that many people still do not know about the adoption process, how inheritance is distributed to adopted children, or how the rights of adopted children comply with the general description of Islamic inheritance law. Many problems occur in society because many people do not know about the rights of adopted children or how to submit a formal claim so that their rights are recognized by the state. In the Compilation of Islamic Law, it is stated that a child's lineage must be carried out by his adoptive parents when he marries and inherits. As a result, adopted children have difficulty understanding their legal position. This research uses normative jurisprudence, namely library research using existing books and references. The solution to problems involving adopted children and adoptive parents is for adoptive parents to understand the legal laws and children's rights as stated in the Compilation of Islamic Law which states that adopted children have the same rights as biological children, including knowing their life history, parents his birth, and the religion of his biological parents and that he was adopted by his adoptive parents.